Pengaruh Profitabilitas, Aktivitas, Leverage, Ukuran Perusahaan, Dewan Direksi Dan Komite Audit Terhadap Pengungkapan Sustainability Report - Retrisya Nioko; Ai Hendrani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Over time, social and environmental issues have become public attention, where the Company is required to pay attention to the environment and surrounding communities. Sustainability report is a standard for assessing the social responsibility of a company. This study aims to determine the effect of Profitability, Activity, Leverage, Company Size, Board of Directors and Audit Committee on Sustainability report. Sampling using purposive sampling techniques obtained 51 data on major sector companies consisting of the agricultural sector and the mining sector in 2020-2022 listed on the Indonesia Stock Exchange (IDX) with analysis using the Statistical Package For Social Science (SPSS) software. The research model uses a causality design and uses multiple linear regression analysis with secondary data types. The results of this study show that the size of the company has a positive influence on the disclosure of sustainability reports. Leverage has a negative influence on sustainability report disclosure. Profitability, activities, the board of directors and the audit committee have no influence on the disclosure of the sustainability report. Further research is recommended to add independent variables, increase the period and expand the sector of the company. This research can provide awareness for companies to disclose sustainability reports, because through these disclosures companies can gain and maintain legitimacy from the community.